1990
DOI: 10.1164/ajrccm/142.1.57
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Elastase and Antielastase Balance in Patients with Chronic Bronchitis and Pulmonary Emphysema

Abstract: On the basis of the "protease-antiprotease imbalance" theory for the pathogenesis of pulmonary emphysema, we hypothesized that measurement of elastase burden and antielastase capacity in the alveolar space might correlate with emphysema. To evaluate this, the severity of emphysema, the elastase burden, and the elastase inhibitory capacity were estimated in 28 patients with chronic bronchitis and variable degrees of emphysema, none of whom had congenital deficiency of alpha-1-protease inhibitor, and all of whom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
71
1
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(77 citation statements)
references
References 13 publications
4
71
1
1
Order By: Relevance
“…This is consistent with the theory that there should be no elastase activity in the presence of active inhibitor. This was also the case in a recent study of neonates with respiratory distress [16], and in bronchitis and emphysema patients [26]. The sum of free and complexed elastase, or elastase load [26], should represent all the elastase released from neutrophils, and be a measure of inflammatory activity in the lungs.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…This is consistent with the theory that there should be no elastase activity in the presence of active inhibitor. This was also the case in a recent study of neonates with respiratory distress [16], and in bronchitis and emphysema patients [26]. The sum of free and complexed elastase, or elastase load [26], should represent all the elastase released from neutrophils, and be a measure of inflammatory activity in the lungs.…”
Section: Discussionmentioning
confidence: 81%
“…This was also the case in a recent study of neonates with respiratory distress [16], and in bronchitis and emphysema patients [26]. The sum of free and complexed elastase, or elastase load [26], should represent all the elastase released from neutrophils, and be a measure of inflammatory activity in the lungs. The close correlation found between it and myeloperoxidase, which is considered to be a good inflammatory marker [27], is confirmation of this.…”
Section: Discussionmentioning
confidence: 81%
“…The most widely accepted theory of the pathogenesis of pulmonary emphysema is a proteinase-antiproteinase imbalance. Although a number of studies have demonstrated the important role of increased elastolytic activity derived from neutrophils in emphysema [4,5], recent studies have shown that matrix metalloproteinases (MMPs) play key roles in tissue remodelling of the airways in COPD and asthma patients [2,[6][7][8]. MMPs are a family of structurally related enzymes that are capable of degrading all components of the ECM [9].…”
mentioning
confidence: 99%
“…KEYWORDS: Bronchial asthma, chronic obstructive pulmonary disease, exacerbation, metalloproteinases, serum markers, tissue inhibitors of matrix metalloproteinases P ulmonary emphysema, the major contributor to morbidity and mortality in patients with chronic obstructive pulmonary disease (COPD), is characterised by progressive destruction of the extracellular matrix (ECM) of the lung [1][2][3][4]. The most widely accepted theory of the pathogenesis of pulmonary emphysema is a proteinase-antiproteinase imbalance.…”
mentioning
confidence: 99%
“…NE released in the lung may be taken up and internalized by alveolar macrophages (AM) (Campbell et al, 1979) . A study evaluating BAL in 28 patients with COPD supported a role for NE and protease-antiprotease imbalance by showing that NE levels in BAL correlated directly and BAL anti-elastase activity correlated inversely with emphysema, assessed by CT scan and carbon monoxide diffusing capacity (Fujita et al,1990). Another study of older volunteers reported increased levels of NE in AM of smokers with CT scan evidence of emphysema (Betsuyaku et al,1995), suggesting that NE release in the lung and its uptake by AM could have been a pathogenic factor in emphysema.…”
Section: Studies Evaluating Neutrophil Elastase In Emphysemamentioning
confidence: 97%